The First Military and Non-Official Pharmacopoeias of the Ottoman Empire - Arslan, Miray; Şar, Sevgi; Sözen Şahne, Bilge (Journal of History Culture and Art Research, 2017)
The first official pharmacopoeia of the Ottoman period was written in 1844 under the title of Pharmacopee Militaire Ottomanee (Pharmacopea Castrensis Otomana) by Austrian Dr. Charles Ambrosie Bernard who was the founder of the first school of pharmacy at that time. This pharmacopoeia was written in French based on 1841 Pharmacopoea Castrensis Austriaca and consists of 161 pages. In this pharmacopoeia, drug names were given in Turkish, Italian and Latin as well as French. Also, in this pharmacopoeia medicinal plants were given in alphabetical order, simple and mixed drugs preparing methods were mentioned and especially focused on pastes but reagents and control methods weren’t mentioned. This book was specifically designed for military hospitals and pharmacies, so, it was not given much of an interest by Istanbul pharmacists. The other codex Düstur-ül Edviye (Drugs Law) which was the translation of 1866 French Codex in Turkish by Major Mr Huseyin Sabri was published in 1874. This codex was printed in Tıbbiye-i Şahane printing house and consisted of 73 chapters and 508 pages. This book replaced the codex which was written by Dr Bernard and has become a guide for Istanbul pharmacists for a long time. In this study, both pharmacopoeias are examined and various aspects of them are discussed.